Programa de liderazgo pedagógico del director para fortalecer la comunidad profesional de aprendizaje de la Institución Educativa 60110 Quistococha, San Juan Bautista 2024 - Gipa Rengifo, Nancy (2025)
Findings are presented in relation to the study after the application of a pedagogical leadership program of the director to strengthen professional learning communities cooperative school management aimed at improving planning competencies, evaluative research, with a single group pre- experimental design that includes pretest and posttest. The population and sample consisted of 30 educators and managers. An instrument validated by specialists was applied, along with a survey and a performance test. The data and information that was collected from the application of a pretest and a posttest were evaluated, interpreted and discussed once the program implementation process was carried out, the research determined the findings, in the post test the majority of the subjects, Specifically, 25 of them reached the excellent category, which constitutes 83.3% of the group. This indicates that the vast majority of participants in the experimental group showed outstanding performance. It is important to note that no subjects with performance outside of these two mentioned categories were recorded. Therefore, it can be concluded that the director's pedagogical leadership program to strengthen the professional learning community has had a positive impact, reflected in the findings obtained in the Post Test.